A message from the field - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Since 1991 a CIRAD/EMVT vet visited the 60 or so goat farms around N`Djamena, Chad, every month. Many of the 3500 small ruminants in these farms suffer from respiratory problems and kid very late. In July 1992 when there was pertly of rain there...